Land management modulates the environmental controls on global earthworm communities. Issue 12 (13th August 2019) - Johnston, Alice S. A.
Abstract: Aim: Soils and their biological communities face increasing pressure from multiple global drivers, including land management and climate change. In soils, earthworms play key roles in ecosystem functioning, but the environmental controls on their global communities are not fully understood. Here, an earthworm dataset was compiled to investigate the effects of environmental variables and land management on global earthworm communities. Location: 40° S–65° N. Time period: 1962 to 2016. Major taxa studied: Earthworms. Methods: A dataset of 899 earthworm community observations, together with environmental variables, was compiled across 169 globally distributed sites. Sites included natural forest and grassland or managed arable, pasture and plantation ecosystems. Total, anecic, endogeic and epigeic abundances and total species richness were compared in natural and managed ecosystems to quantify the effects of land management across climates. A hierarchical model was used to test the importance of environmental controls in predicting the relationship between total earthworm species richness and abundance at a global scale. Results: Land management prompted little change in total earthworm abundance at the global scale, but reduced species richness and shifted community composition. Endogeic earthworms were more abundant in managed ecosystems, while anecic and epigeic earthworms showed variable responses across ecosystem types. Global relationships between total earthworm species richness and abundance were explained by climate, soil pH and land management. Main conclusions: Land management modulates the effects of environmental controls on global earthworm communities, through direct disturbance and indirect changes in edaphic conditions.